Harley-Davidson Motor Company : bonding with the biker - Townsend, Stephanie; Beder, Laurence ([London] : SAGE, 2016)
Since 1996, when international motorcycle manufacturer Harley-Davidson first established a presence in South Africa, the company had grown from only one dealership to seven independent dealerships in 2007. Although Harley owners were mostly male, five years previously, South African dealerships had been the first to act on a concerted global Harley strategy to penetrate the female market. The move had been successful, and there were now proportionally more female Harley owners in South Africa than in any other country. This case study discusses this topic.
Originally Published in: Townsend, S. & Beder, L. (2007). Harley-Davidsonr Motor Company: Bonding with the Biker. WBS 2007-3. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Harley-Davidson Motor Company; Brand name products -- Marketing -- Case studies; Marketing -- Case studies; Women consumers -- Case studies